Determinants Of Online Purchase Intention Of Seasonal Goods In Nigeria: The Role Of Perceived Value And Trust - Nwakaji, Christopher (2023)
Seasonality influenced every aspect of consumer purchase decisions. Seasons determine the goods that consumers purchase, and when to purchase them. The last few decades have experienced tremendous growth in online purchases, especially during the seasonal periods in Nigeria. Despite this growth in online purchases, the factor influencing consumer online purchase intention of seasonal goods remained under-researched. This study aims to examine the mediating effect of perceived value and trust on the relationship between perceived economic benefit, perceived transaction security, compatibility, website quality, price image, perceived vendor transparency, brand image and online purchase intention of seasonal goods. The theories underpinning this study are the Stimulus Organism Response Theory (SOR) and the Value-Based Adoption Model (VAM). A survey questionnaire was the major instrument used to collect primary data for this study. A mall intercept method was used to administer the questionnaire to the participants. Questionnaires were administered to 800 online shoppers purposively selected from shopping malls across the six geopolitical zones of the country. After data screening, 413 questionnaires were found usable. The study used a Statistical Package for Social Sciences and the Smart PLS-SEM to analyse the data. The results of data analysis revealed that perceived economic benefit, perceived transaction security, compatibility, website quality, price image and brand image have a positive effect on consumer trust. Similarly, perceived transaction security, compatibility, website quality, price image and brand image have positive effects on perceived value.